2016
DOI: 10.4103/2008-322x.194131
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic retinopathy clinical practice guidelines: Customized for Iranian population

Abstract: Purpose:To customize clinical practice guidelines (CPGs) for management of diabetic retinopathy (DR) in the Iranian population.Methods:Three DR CPGs (The Royal College of Ophthalmologists 2013, American Academy of Ophthalmology [Preferred Practice Pattern 2012], and Australian Diabetes Society 2008) were selected from the literature using the AGREE tool. Clinical questions were designed and summarized into four tables by the customization team. The components of the clinical questions along with pertinent reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 321 publications
(248 reference statements)
0
7
0
Order By: Relevance
“…International Council of Ophthalmology Guidelines for Diabetic Eye Care was translated to Farsi and introduced to participants as the instructional material [ 14 ]. Other sources included Clinical Practice Guidelines for Iranian Population and the Online Self-Directed Diabetic Retinopathy Grading Course affiliated to the University of Melbourne [ 17 , 26 ]. The participants were assessed by both formative and summative evaluation methods during and at the end of the course.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…International Council of Ophthalmology Guidelines for Diabetic Eye Care was translated to Farsi and introduced to participants as the instructional material [ 14 ]. Other sources included Clinical Practice Guidelines for Iranian Population and the Online Self-Directed Diabetic Retinopathy Grading Course affiliated to the University of Melbourne [ 17 , 26 ]. The participants were assessed by both formative and summative evaluation methods during and at the end of the course.…”
Section: Methodsmentioning
confidence: 99%
“…DR meets the Wilson and Jungner criteria for evaluating the needs of a screening program [ 13 ]. The WHO, International Council of Ophthalmology (ICO), clinical guidelines, and the National Program for Prevention and Control of Diabetes (NPPCD) have recommended regular eye examinations in patients with DM [ 14 – 17 ]. Despite these recommendations, population-based studies performed in Iran have reported a gap in regular eye examination in individuals with DM [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic retinopathy (DR) is a devastating ocular impediment and the leading cause of vision loss among working-age adults in developed countries 21. Worldwide, the prevalence of DR has been predicted to be 35% and the prevalence of vision-impairing is estimated around 10% 22, 23. Various risk factors such as poor glycaemic control, hypertension, hyperlipidaemia, longer diabetes duration and albuminuria are reported to be the origination and development of DR 24, 25.…”
Section: Malat1 In Diabetes-related Complicationsmentioning
confidence: 99%
“…The evidence shows that PRP may induce DME or exacerbate preexisting DME. 15,16,18 Peripheral VF loss is the other concern regarding application of PRP for treatment of PDR. 19 Proliferative diabetic retinopathy control can be achieved through frequent intravitreal anti-VEGF injections.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence shows that PRP may induce DME or exacerbate preexisting DME. 15,16,18 Peripheral VF loss is the other concern regarding application of PRP for treatment of PDR. 19…”
Section: Discussionmentioning
confidence: 99%